Composite material for safety helmet, preparation method of composite material and safety helmet

By using composite materials of unsaturated polyester and glass fiber for molding, and adding titanium silicon carbide and modified titanium silicon carbide, the heat resistance of safety helmets in high temperature environments is solved, and the production efficiency and overall product are improved. performance.

CN119431698APending Publication Date: 2025-02-14ZHEJIANG WANXING NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411569098.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing safety helmets are prone to melt in high temperature environments, affecting their impact resistance. The traditional glass fiber hand paste process is unstable in quality and has many processes, which reduces production efficiency.

Method used

Using composite materials of unsaturated polyester and glass fiber, safety helmets are directly prepared by molding, adding titanium silicon carbide and modified titanium silicon carbide to improve heat resistance, and simplifying the process by adding inner coloring pigments.

Benefits of technology

It improves the heat resistance and production efficiency of the safety helmet, ensures the stability of quality and uniformity of thickness, and significantly improves the impact toughness and bending strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119989810000071
    Figure BDA0005119989810000071
Patent Text Reader

Abstract

The invention relates to the technical field of safety helmets, in particular to a composite material for a safety helmet, a preparation method of the composite material and the safety helmet. The composite material for the safety helmet is prepared from the following raw materials in parts by weight: 22 to 27 parts of unsaturated polyester, 4 to 6 parts of low-profile shrinking agent, 0.4 to 0.8 part of high-activity initiator, 1.6 to 2.4 parts of internal release agent, 0.2 to 0.6 part of thickening agent, 25 to 35 parts of flame retardant, 25 to 35 parts of glass fiber, 0 to 5 parts of internal coloring pigment and 2 to 6 parts of auxiliary agent. The safety helmet has the advantage that the heat resistance and the production efficiency of the safety helmet are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of safety helmets, and in particular to a composite material for a safety helmet, a preparation method thereof, and a safety helmet. Background Art

[0002] Safety helmets can protect workers from impacts and provide a degree of safety. However, in high-temperature workplaces, such as steel mills, hot objects are often present. Contact with these objects can cause the helmet to melt, compromising its impact resistance.

[0003] To improve the heat resistance of safety helmets, traditional technology involves manually applying a layer of fiberglass to the surface. However, this process can lead to inconsistent quality and uneven thickness. Furthermore, the subsequent application of the fiberglass layer requires painting, which increases the production process and reduces production efficiency. Summary of the Invention

[0004] In order to improve the heat resistance and production efficiency of a safety helmet, the present application provides a composite material for a safety helmet, a preparation method thereof, and a safety helmet.

[0005] In a first aspect, the present application provides a composite material for a safety helmet, which adopts the following technical solution: A composite material for a safety helmet comprises the following raw materials in parts by weight: 22-27 parts of unsaturated polyester, 4-6 parts of a low-profile shrinkage agent, 0.4-0.8 parts of a high-activity initiator, 1.6-2.4 parts of an internal release agent, 0.2-0.6 parts of a thickener, 25-35 parts of a flame retardant, 25-35 parts of glass fiber, 0-5 parts of an internal coloring pigment, and 2-6 parts of an auxiliary agent.

[0006] By adopting the above technical solution, the composite material prepared by the present application through the selection of the amount of unsaturated polyester and glass fiber can be directly molded, without the need to manually hand-lay a layer of glass fiber after the safety helmet is prepared to improve the heat resistance. Moreover, the safety helmet prepared by the present application has more stable quality, more uniform thickness, and better heat resistance than the manual hand-laid glass fiber. In addition, the present application can be colored by adding internal coloring pigments, and there is no need to carry out the painting step after the hand-laid glass fiber, which simplifies the process, reduces costs, and improves production efficiency. According to the actual production data of the factory, the composite material prepared by the present application is produced into a safety helmet through molding, which is 10 times the production efficiency of the safety helmet prepared by manual hand-laying.

[0007] Preferably, the composite material for a safety helmet further comprises 1-4 parts by weight of titanium silicon carbide, and the particle size of the titanium silicon carbide is ≤20 μm.

[0008] By adopting the above technical solution, titanium silicon carbide is a new material with broad application prospects in the high-temperature field. It combines the advantages of ceramic materials and metal materials, and has high-temperature resistance, oxidation resistance, high strength, good thermal conductivity, workability and plasticity. The inventors of this application added it to the composite materials for safety helmets. It can be seen that it can indeed significantly improve the high-temperature resistance of the safety helmet and effectively reduce the impact force of the head mold after high-temperature treatment.

[0009] Preferably, the titanium silicon carbide is modified titanium silicon carbide, which is prepared by coupling titanium silicon carbide with a hydroxyl-containing silane coupling agent and then in-situ grafting a hyperbranched polyamide-ester containing double bond groups through an esterification reaction.

[0010] By adopting the above technical solution, since titanium silicon carbide is still an inorganic material, its bonding ability with the composite material is low, there is a large interfacial tension, and its compatibility with the system is poor, resulting in a decrease in the integrity of the composite material, and a decrease in the bending strength and impact toughness of the composite material. And as its addition amount gradually increases, its head mold impact force shows a trend of first decreasing and then increasing. On this basis, the inventors modified titanium silicon carbide and grafted a hyperbranched polyamide-ester containing double bonds on its surface. On the one hand, it can improve its compatibility with unsaturated resins and reduce interfacial tension; on the other hand, the double bonds contained in its hyperbranched polyamide-ester can participate in the polymerization reaction of the system, thereby allowing titanium silicon carbide to form a cross-linking center and improve the cross-linking degree of the system. These two effects not only make up for the reduction in mechanical properties brought about by titanium silicon carbide, but also can effectively improve the heat resistance of the safety helmet.

[0011] As a preference: the preparation method of the hyperbranched polyamide-ester is as follows: S1. Weigh 1.5-2.5 mol of diethanolamine and add DMAC to completely dissolve it to obtain a diethanolamine solution; weigh 1.3-1.6 times the molar amount of diethanolamine in maleic anhydride and add DMAC to completely dissolve it to obtain a maleic anhydride solution; S2. Under a nitrogen atmosphere, the maleic anhydride solution is added dropwise to the diethanolamine solution while stirring. After the addition is complete, the stirring reaction is continued for 5-8 hours. After the reaction is complete, the solvent and unreacted monomer are removed by distillation under reduced pressure to obtain a polyamide-ester monomer; S3. Under a nitrogen atmosphere, add the polyamide-ester monomer to DMAC until the polyamide-ester is completely dissolved, add 400-700 mL of toluene as a water-carrying agent, add 0.005-0.008 mol of p-toluenesulfonic acid as a catalyst, and stir until dissolved to obtain solution A. S4. Weigh 0.01-0.02 mol of glycerol, add DMAC until the glycerol is completely dissolved, and then add it dropwise to solution A. At the same time, raise the temperature to 150-160° C. and reflux for 20-28 hours until no liquid drops. Then, distill under reduced pressure to remove the solvent and unreacted raw materials to obtain a hyperbranched polyamide-ester.

[0012] By adopting the above technical solution, a hyperbranched polyamide-ester with double bonds and carboxyl groups is synthesized, which can be in situ grafted with the surface-treated titanium silicon carbide through the carboxyl groups and can participate in the polymerization reaction of the system through the double bonds.

[0013] Preferably, the particle size of the titanium silicon carbide is 10 μm.

[0014] By adopting the above technical solution, the particle size of titanium silicon carbide is an important factor affecting the performance of the composite material, and the optimal particle size is 10 μm.

[0015] Preferably, the hydroxyl-containing silane coupling agent is bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane.

[0016] In a second aspect, the present application provides a method for preparing a composite material for a safety helmet, which adopts the following technical solution: A method for preparing a composite material for a safety helmet comprises the following steps: S1. Mix the unsaturated polyester and the low-profile shrinkage agent, then add the high-activity initiator and the auxiliary agent, and continue to stir and mix; then add the internal coloring pigment, the internal release agent, the flame retardant and the remaining raw materials except the thickener in sequence, and stir and mix; S2. Finally, add the thickener and stir to obtain a mixture; S3. The mixture obtained in S2 is aged in a drying room at 35-45° C. for 48 hours. After the aging, the mixture is stacked according to the thickness and cured in a high-temperature mold at a temperature of 12-140° C. to obtain an explosion-proof box composite material.

[0017] By adopting the above technical solution, in the preparation method of the present application, stirring and mixing can be carried out in the order of addition. The preparation method is relatively conventional and does not require special processes or equipment modification. The prepared composite material has high uniformity and a high pass rate, and is suitable for large-scale production.

[0018] In a third aspect, the present application provides a method for preparing a composite material for a safety helmet, which adopts the following technical solution: a safety helmet, wherein the safety helmet is made of a composite material for a safety helmet according to any one of claims 1-6.

[0019] In summary, this application includes at least one of the following beneficial technical effects: 1. The composite material prepared by the present application through the selection of the amount of unsaturated polyester and glass fiber can be directly molded, without the need to manually lay up a layer of glass fiber after the safety helmet is prepared to improve the heat resistance. Moreover, the safety helmet prepared by the present application has more stable quality, more uniform thickness, and better heat resistance than the glass fiber laid up by hand. In addition, the present application can be colored by adding internal coloring pigments, without the need for a painting step after the glass fiber is hand laid up, which simplifies the process, reduces costs, and improves production efficiency. According to the actual production data of the factory, the composite material prepared by the present application is molded to produce safety helmets, which is 10 times the production efficiency of the safety helmets prepared by manual hand laying.

[0020] 2. By modifying titanium silicon carbide and grafting a hyperbranched polyamide-ester containing double bonds onto its surface, the researchers can improve its compatibility with unsaturated resins and reduce interfacial tension. Furthermore, the double bonds in the hyperbranched polyamide-ester can participate in the polymerization reaction, allowing the titanium silicon carbide to form crosslinking centers and increase the crosslinking degree of the system. These two effects not only compensate for the reduction in mechanical properties caused by titanium silicon carbide, but also effectively improve the heat resistance of the safety helmet.

[0021] 3. The safety helmet made of the composite material produced in this application has a head mold impact force of 2172N after high temperature, which greatly improves the high temperature resistance of the safety helmet and improves safety; at the same time, the maximum bending strength of the composite material can reach 248MPa and the impact toughness can reach 165kJ / m 2 . DETAILED DESCRIPTION

[0022] The following is a further detailed description of this application in conjunction with the specific content.

[0023] raw material The raw materials used in the preparation examples and embodiments of this application can all be purchased commercially, among which the model of unsaturated polyester is 196; the high-activity initiator is TBPO, with a content of 97%; the low-profile shrinkage agent is polystyrene, model H814-902; the internal release agent is zinc stearate, CAS No. 557-05-1; the thickener is activated magnesium oxide, model 600; the flame retardant is aluminum hydroxide, with a particle size of 8000 mesh; the model of the auxiliary agent is BYK-301; the internal coloring pigment is cobalt blue, model 001; and the glass fiber is alkali-free glass fiber, with a length of 3.0 mm.

[0024] Preparation Example Preparation Example 1 A modified titanium silicon carbide, the preparation method of which is as follows: S1. Weigh 2 mol of diethanolamine and add an appropriate amount of DMAC until the diethanolamine is completely dissolved to obtain a diethanolamine solution; weigh 3 mol of maleic anhydride and add an appropriate amount of DMAC until the maleic anhydride is completely dissolved to obtain a maleic anhydride solution; S2. Under a nitrogen atmosphere, the maleic anhydride solution was added dropwise to the diethanolamine solution at a dropping rate of 1.5 mL / min with stirring. After the addition was complete, the stirring reaction was continued for 6 h. After the reaction was complete, the solvent and unreacted monomer were removed by distillation under reduced pressure to obtain a polyamide-ester monomer; S3. Under a nitrogen atmosphere, add a polyamide-ester monomer to an appropriate amount of DMAC until the polyamide-ester is completely dissolved. Then, add 20 mL of toluene as a water carrier and 1.1 g of p-toluenesulfonic acid as a catalyst, and stir until dissolved to obtain solution A. S4. Weigh 0.013 mol of glycerol, add an appropriate amount of DMAC until the glycerol is completely dissolved, and then add the mixture dropwise to solution A at a rate of 0.8 mL / min. Simultaneously, raise the temperature to 155° C., reflux for 24 h until no liquid drops, and remove the solvent and unreacted raw materials by distillation under reduced pressure to obtain a hyperbranched polyamide-ester. S5. Disperse 1 g of titanium silicon carbide in 200 mL of a mixed solution of ethanol and deionized water in a volume ratio of 1:1. After ultrasonic dispersion, add 0.5 g of bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane. Stir and react at room temperature for 24 h. Centrifuge at 2000 r / min, discard the supernatant, wash the precipitate with deionized water, and vacuum dry to obtain silane coupling agent-grafted titanium silicon carbide; wherein the particle size of the titanium silicon carbide is 5 μm; S6. Weigh 100 g of hyperbranched polyamide-ester, add an appropriate amount of DMAC to completely dissolve it, then add 40 mL of toluene as a water-carrying agent and 0.6 g of p-toluenesulfonic acid as a catalyst, and stir until dissolved to obtain solution B; 8 g of silane coupling agent-grafted titanium silicon carbide was dispersed in 50 g of DMAC and ultrasonically dispersed; solution B was heated to 150° C. and added to solution B in a nitrogen atmosphere in 5 times, with an interval of 10 minutes between two adjacent additions. After the addition, stirring was continued for 20 hours, the mixture was cooled to room temperature, and centrifuged at a speed of 2000 r / min. The supernatant was discarded, and the precipitate was washed with DMAC and then with ethanol, and vacuum dried at room temperature to obtain modified titanium silicon carbide.

[0025] Preparation Example 2 A modified titanium silicon carbide is different from Preparation Example 1 in that the particle size of the titanium silicon carbide is 10 μm, and the remaining steps are the same as Preparation Example 1.

[0026] Preparation Example 3 A modified titanium silicon carbide is different from Preparation Example 1 in that the particle size of the titanium silicon carbide is 20 μm, and the remaining steps are the same as Preparation Example 1. Example

[0027] Example 1 A composite material for a safety helmet, the raw materials and amounts of which are shown in Table 1, and the preparation method thereof is as follows: S1. Mix unsaturated polyester and low profile shrinkage agent at 30°C and stir for 45 seconds, then add high activity initiator and auxiliary agent, and continue stirring for 30 seconds; S2, continue to add internal coloring pigment and stir for 30s; S3, continue to add internal release agent and stir for 30 seconds; S4. Raise the temperature to 34.5°C, add the flame retardant, and stir for 90 seconds; S5. Raise the temperature to 36.5°C, add the thickener, and stir for 60 seconds to obtain a mixture; S6. The mixture obtained in S5 is cured in a drying room at 40° C. for 48 hours. After curing, the mixture is stacked according to thickness and cured in a high-temperature mold at 130° C. for 8 minutes to obtain an explosion-proof box composite material.

[0028] Table 1 Raw materials and amounts of raw materials used in Example 1 (kg) Unsaturated polyester 25 Low profile shrinkage agent 5 Highly active initiator 0.6 Internal release agent 2 thickener 0.4 flame retardants 30 fiberglass 30 Internal coloring pigments 3 additives 4 Example 2 A composite material for a safety helmet differs from Example 1 in that its raw materials further include 1 kg of titanium silicon carbide with a particle size of 10 μm, which is added at the same time as the flame retardant. The remaining steps are the same as those in Example 1.

[0029] Example 3 A composite material for a safety helmet is different from Example 1 in that the raw materials further include 2 kg of titanium silicon carbide, the particle size of titanium silicon carbide is 10 μm, and the remaining steps are the same as Example 1.

[0030] Example 4 A composite material for a safety helmet is different from Example 1 in that the raw materials further include 3 kg of titanium silicon carbide, the particle size of titanium silicon carbide is 10 μm, and the remaining steps are the same as Example 1.

[0031] Example 5 A composite material for a safety helmet, which differs from Example 3 in that its titanium silicon carbide is replaced by modified titanium silicon carbide of equal mass, and the modified titanium silicon carbide comes from Preparation Example 1. The remaining steps are the same as those of Example 3.

[0032] Example 6 A composite material for a safety helmet, which differs from Example 3 in that titanium silicon carbide is replaced by modified titanium silicon carbide of equal mass, the modified titanium silicon carbide comes from Preparation Example 2, and the remaining steps are the same as Example 3.

[0033] Example 7 A composite material for a safety helmet, which differs from Example 3 in that its titanium silicon carbide is replaced by modified titanium silicon carbide of equal mass, and the modified titanium silicon carbide comes from Preparation Example 3. The remaining steps are the same as Example 3.

[0034] Example 8 A composite material for a safety helmet is different from Example 6 in that the amount of modified titanium silicon carbide added is 3 kg, and the remaining steps are the same as Example 6.

[0035] Example 9 A composite material for a safety helmet, which is different from Example 6 in that the amount of modified titanium silicon carbide added is 4 kg, and the remaining steps are the same as Example 6.

[0036] Comparative Example Comparative Example 1 A composite material for a safety helmet, which is different from Example 2 in that the particle size of titanium silicon carbide is 30 μm, and the remaining steps are the same as Example 2.

[0037] Application Examples Application Examples 1-9 A safety helmet is obtained by sequentially applying the composite materials for helmets of Examples 1 to 9 through molding.

[0038] Performance testing Detection method / test method Composite materials for safety helmets were prepared according to the preparation methods of Examples 1-9 and Comparative Example 1, and then tested according to the following test method. The test results are shown in Table 2.

[0039] Bending strength: tested according to the test method in GB / T1449-2005; Impact toughness (unnotched): tested in accordance with the test method in GB / T1451-2005.

[0040] The safety helmets of Application Examples 1-9 were tested according to the test methods in GB2811-2019 "Head Protection Safety Helmets", and the test results were all qualified. The impact test data of the extreme high temperature resistance performance of the safety helmets of Application Examples 2-9 are shown in Table 2. In the impact test, it is stipulated that the impact test should be carried out after pretreatment at an extreme high temperature of 150°C for 1h. The force transmitted to the head mold should not be greater than 4900N, and no fragments of the helmet shell should fall off to be qualified.

[0041] Table 2 Test results of Examples 1-9 and Comparative Example 1 Through Examples 1-9, Comparative Example 1 and Application Examples 1-9, and the test data in Table 2, it can be seen that the composite material prepared by the present application through the selection of the amount of unsaturated polyester and glass fiber can be directly molded, and there is no need to manually lay up a layer of glass fiber after the safety helmet is prepared to improve the heat resistance. And the safety helmet prepared by the present application is more stable in quality and more uniform in thickness compared to the manual hand-laid glass fiber. In addition, the present application can be colored by adding internal coloring pigments, and there is no need to carry out the painting step after the hand-laid glass fiber, which simplifies the process, reduces costs, and improves production efficiency. According to the actual production data of the factory, the composite material prepared by the present application is molded to produce safety helmets, which is 10 times the production efficiency of the safety helmet prepared by manual hand-laying. And the safety helmet prepared by the composite material produced by the present application has a head mold impact force of 2172N after high temperature, which greatly improves the high temperature resistance of the safety helmet and improves safety; at the same time, the bending strength of the composite material can reach a maximum of 248MPa, and the impact toughness can reach 165kJ / m 2 .

[0042] Titanium silicon carbide is a new material with broad application prospects in high-temperature applications. It combines the advantages of ceramic and metallic materials, offering high-temperature resistance, oxidation resistance, and high strength, as well as good thermal conductivity, workability, and plasticity. The inventors of this application have added it to composite materials for safety helmets, demonstrating that it can significantly improve the safety helmet's high-temperature resistance and effectively reduce the headform impact force after high-temperature treatment. However, because titanium silicon carbide is still an inorganic material, its bonding ability with composite materials is relatively low, resulting in high interfacial tension and poor compatibility with the system. This reduces the overall integrity of the composite material, resulting in a decrease in the composite material's flexural strength and impact toughness. Furthermore, as the amount of titanium silicon carbide added increases, its headform impact force shows a trend of first decreasing and then increasing. This is speculated to be due to excessive addition and poor compatibility, which reduces the mechanical properties of the safety helmet. This can be verified by the test data of Examples 1-4. On this basis, the inventors modified titanium silicon carbide by grafting a hyperbranched polyamide-ester containing double bonds onto its surface. This, on the one hand, improves its compatibility with unsaturated resins and reduces interfacial tension; on the other hand, the double bonds contained in the hyperbranched polyamide-ester can participate in the polymerization reaction of the system, thereby forming crosslinking centers in the titanium silicon carbide and increasing the crosslinking degree of the system. This two-pronged effect not only compensates for the reduction in mechanical properties caused by titanium silicon carbide, but also effectively improves the heat resistance of the safety helmet. This can be verified by combining the test data of Examples 3 and 5.

[0043] The test data of Example 2, Examples 5-7, and Comparative Example 1 show that the particle size of titanium silicon carbide is an important factor affecting the performance of the composite material, and its particle size should not exceed 20 μm.

[0044] It can be seen from the test data of Example 6 and Examples 8-9 that the optimal addition amount of modified titanium silicon carbide is 3 kg.

[0045] This specific embodiment is merely an explanation of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by patent law.

Claims

1. A composite material for a safety helmet, characterized in that: The invention comprises the following raw materials in parts by weight: 22-27 parts of unsaturated polyester, 4-6 parts of low profile shrinkage agent, 0.4-0.8 parts of high activity initiator, 1.6-2.4 parts of internal mold release agent, 0.2-0.6 parts of thickener, 25-35 parts of flame retardant, 25-35 parts of glass fiber, 0-5 parts of internal coloring pigment and 2-6 parts of auxiliary agent.

2. The composite material for a safety helmet according to claim 1, characterized in that: The composite material for a safety helmet further comprises 1-4 parts by weight of titanium silicon carbide, and the particle size of the titanium silicon carbide is ≤20 μm.

3. A composite material for a safety helmet according to claim 2, characterized in that: The titanium silicon carbide is modified titanium silicon carbide, which is prepared by coupling titanium silicon carbide with a hydroxyl-containing silane coupling agent and then in-situ grafting a hyperbranched polyamide-ester containing a double bond group through an esterification reaction.

4. The composite material for a safety helmet according to claim 3, characterized in that: The preparation method of the hyperbranched polyamide-ester is as follows: S1, weigh 1.5-2.5 mol of diethanolamine, add DMAC to completely dissolve it, and obtain a diethanolamine solution; weigh 1.3-1.6 times the molar amount of diethanolamine maleic anhydride, add DMAC to completely dissolve it, and obtain a maleic anhydride solution; S2. Under a nitrogen atmosphere, the maleic anhydride solution is added dropwise to the diethanolamine solution while stirring. After the addition is complete, the stirring reaction is continued for 5-8 hours. After the reaction is complete, the solvent and unreacted monomers are removed by distillation under reduced pressure to obtain a polyamide-ester monomer; S3. Under a nitrogen atmosphere, add the polyamide-ester monomer to DMAC until the polyamide-ester is completely dissolved, add 400-700 mL of toluene as a water carrier, add 0.005-0.008 mol of p-toluenesulfonic acid as a catalyst, and stir until dissolved to obtain solution A; S4, weigh 0.01-0.02 mol of propylene glycol, add DMAC until the propylene glycol is completely dissolved, then add it dropwise to solution A, and at the same time raise the temperature to 150-160° C., reflux for 20-28 hours until no liquid drops, and distill under reduced pressure to remove the solvent and unreacted raw materials to obtain hyperbranched polyamide-ester.

5. The composite material for a safety helmet according to claim 3, characterized in that: The particle size of the titanium silicon carbide is 10 μm.

6. The composite material for a safety helmet according to claim 3, characterized in that: The hydroxyl-containing silane coupling agent is bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane.

7. A method for preparing the composite material for a safety helmet according to any one of claims 1 to 6, characterized in that: It includes the following steps: S1, mixing unsaturated polyester and low profile shrinkage agent, then adding high activity initiator and auxiliary agent, and continuing to stir and mix; then sequentially adding internal coloring pigment, internal release agent, flame retardant and remaining raw materials except thickener, and stirring and mixing; S2, finally add thickener, stir to obtain a mixture; S3. The mixture obtained in S2 is aged in a drying room at 35-45° C. for 48 hours. After the aging, the mixture is stacked according to the thickness and cured in a high-temperature mold at a temperature of 12-140° C. to obtain an explosion-proof box composite material.

8. A safety helmet, characterized in that: The safety helmet is made of the composite material for a safety helmet according to any one of claims 1 to 6.

Citation Information

Cited By

  • Degradable bamboo wood pulp composite material, production method thereof and application of degradable bamboo wood pulp composite material in safety helmet production

    CN120865724A